The Number of Limit Cycles in a Class of Piecewise Polynomial Systems (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we pay attention to the number of limit cycles for aclass of piecewise smooth near-Hamiltonian systems. By using the expressionof the first order Melnikov function and some known results about Chebyshev systems, we study upper bound of the number of limit cycles in Hopfbifurcation and Poincaré bifurcation respectively.
Keywords: Piecewise smooth system; Melnikov function; ECT-system; Limit cycle.